FOLIAR OR CHEMICAL FERTILIZERS FOR GARDEN PEAS - Ion BOZGA; Oli mpia PANDIA; Ion SARACIN; Ioan Christi GANEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2015)
The main objective of this paper was the research and controlled study of the main physiological processes of the garden pea, the type Redondo, with the purpose of knowing adaptability the natural conditions in the area. In this purpose, was observed the special behavior of the garden pea Redondo, at the meteorological conditions that exist in this study (temperature, moist, light intensity) determining physiological that took place: photosynthesis, chlorophyll, perspiration, absorption and index of the foliar surface. During the vegetation have been realized observations regarding: moment of arising, apparition of the first real leaves, dynamics of formation leaves and their dimensions, the number of plant leaves, formation of ramification of the roots, apparition of the floral buds, opening flowers, formation of fruits and reaching full maturity.